Effects of Lespedeza Cuneata aqueous extract on testosterone-induced prostatic hyperplasia - Bong Kyun Park; Chang Won Kim; Jeong Eun Kwon; Manorma Negi; Yong Tae Koo; Sang Hun Lee; Dong Hyun Baek; Yoo Hun Noh; Se Chan Kang (Taylor & Francis Group, 2019)
Context: Lespedeza cuneata G. Don (Fabaceae), has been used as a traditional treatment of various diseases. There is a report L. cuneata effects on hormone replacement therapy for endocrine-related disease. However, studies related to benign prostatic hyperplasia (BPH) have not been investigated. Objective: The effects of L. cuneata aqueous extract (LCW) on testosterone-induced prostatic hyperplasia (TPH) were examined. Materials and methods: Male Wistar rats (10 weeks, 330-350 g) were randomly divided to 6 groups (n = 6): Control group; TPH group (3 mg/kg, s.c, daily); TPH + LCW (25, 50, 100 mg/kg); TPH + Finasteride 10 mg/kg for 6 weeks. At the end of treatment, histological change of prostate, serum dihydrotestosterone (DHT) level, mRNA expression of 5α-reductase, inflammatory factors, proliferating cell nuclear antigen (PCNA) and fibroblast growth factor-2 (FGF-2) in prostate were examined. Then, LCW was treated with BPH-1, a human BPH cell line, at 25, 50, 100 μg/mL for 24 h and examine mRNA level of androgen receptor (AR) and prostate-specific antigen (PSA). In addition, the content of vicenin-2 was analyzed. Results: LCW treatment of TPH inhibited serum DHT levels by 54.5, 51.2 and 54.1% and mRNA expression of 5α-reductase were inhibited 54.3, 61.3 and 73.6%, respectively. In addition, mRNA expression of inflammatory factors, PCNA and FGF-2 were decreased in the prostate of rats. Also, LCW attenuated mRNA level of AR and PSA in BPH-1 cell. The content of vicenin-2 in the LCW was analyzed to 0.89 mg/g. Discussion and conclusions: Based on the results, LCW is a potential pharmacological candidate for the treatment of prostatic hyperplasia.